The determinants of exchange rate: case of Malaysia / Muhammad Abdul Afiq Abdul Mutalib and Muhammad Asyraf Mohd Rosli - Abdul Mutalib, Muhammad Abdul Afiq; Mohd Rosli, Muhammad Asyraf (Faculty of Business and Management, 2016)
The aim of this study is to investigate the relationship between External Debt, Oil price, Inflation Rate and GDP to the Exchange rate of Malaysia. The study used Simple Linear Regression and Multiple Linear Regression in order to find the relationship among those markets. The yearly data is collected from 1980 until 2015. From the result, it reveals that GDP and External Debt have a negative relationship towards Exchange Rate. But, only GDP has a significant relationship towards exchange rate. The other variables, Oil Price and Inflation Rate have a insignificant positive relationship to the Exchange Rate. These results further our understanding of the relationship between the macroeconomics variables should be useful for regulator, investor and speculator.